Who Owns the Unexpected? Insights from Antigone for Don Lamberton's economic question. (1st December 2015) - Williams, Ruth F.G.
Abstract : Dissent and assent contribute to new information and knowledge in that they foster ideas, avert errors and counter misplaced beliefs. Although intended to facilitate progress, innovation and creativity, dissent may be opposed by the closed mind and defensive mindset. Don Lamberton encountered a specific mindset in his own duties to scholarship in economics. Thus, the perspective of dissent is a fitting way to pay homage to his scholarship. However, this paper is also a lament. It gives an interpretation of Antigone from political philosophy which depicts Antigone rocking an ideological boat harboured by the polis . The silencing of Antigone's voice results in unexpected losses in the oikos . This is the sort of tragedy threatening critical and innovative scholarship in the twenty-first century.